Pathological, immunological and molecular epidemiological analysis of lumpy skin disease virus in Indian cattle during a high-mortality epidemic - Gundallhalli Bayyappa Manjunathareddy; Mani Saminathan; Lalasangi Sanjeevakumar; Sugana Rao; Murali Dinesh; Kuldeep Dhama; Karam Pal Singh; Bhupendra Nath Tripathi (Veterinary Quarterly)
Lumpy skin disease (LSD) is an economically significant, emerging viral disease of Cattle and Buffaloes. This study aimed to investigate the causes of high mortality in a recent LSD epidemic in India. We examined 1618 animals across seventy outbreaks and conducted post-mortem on 48 cattle out of 513 clinically suspected LSD cases. The morbidity, mortality and case fatality rates recorded were 31.70%, 2.97 and 9.37% respectively. Disease stages were categorized as early (20.81%), mid (42.02%), and late (37.17%) and the distribution of skin lesions was classified as mild (34.14%), moderate (39.39%), and severe (26.47%). Post-mortem findings revealed systemic infection with necrotic and ulcerative nodules on multiple internal organs. Histologically, necrotizing vasculitis and mononuclear cell infiltration with intracytoplasmic inclusions were observed in various organs. The highest viral load was found in skin nodules/scabs, trachea, tongue, and lymph nodes. The viral load was significantly higher in mid- and late-stages of skin nodules and internal organs; whereas, blood from early-stage showed high viral load. The expression of Th1-type and Th2-type cytokines varied significantly across different stages of the disease. The downregulation of the apoptotic intrinsic and upregulation of the extrinsic pathway genes, suggesting that the latter plays a role in LSDV infection. Genetic analysis revealed that the LSD virus (LSDV) isolates were derived from a Kenyan ancestral strain with unique nucleotide changes in RPO30 and P32 gene. In conclusion, the high mortality in the recent Indian LSD epidemic can be attributed to a newly identified, highly virulent strain of LSDV causing systemic infection.